PERBEDAAN KADAR KREATININ METODE JAFFE REACTION PADA SERUM SEGERA DAN SIMPAN SELAMA 1, 2, DAN 3 HARI PADA SUHU RUANG - Salsabila Widayat, Niva (Jurnal Kesehatan Siliwangi, 2024)
The laboratory examination stage consists of pre-analytical, analytical and post-analytical stages. One of the laboratory examination stages is the pre-analytical stage, where this stage has the largest error percentage, namely 77.1%. Checking creatinine levels is one of the tests to determine kidney function. This study aims to determine differences in serum creatinine levels immediately and stored for 1, 2 and 3 days at room temperature. This research was conducted in April 2024 at the Clinical Chemistry Laboratory, Technology Medical Laboratory, Health Polytechnic, Ministry of Health, Bandung. This research was quasi-experimental in nature by providing treatment in the form of storing serum after centrifugation for 1, 2, and 3 days at room temperature and then the levels were compared with the serum levels which were immediately examined. This examination was examined using the Jaffe reaction method using a photometer with a wave length of 505 nm and repeated in triplicate so that 72 data were obtained which were then processed using SPSS with the general linear model (GLM) test. The results of the study showed that the creatinine examination showed an average immediate serum value of 0.88 mg/dL and stored serum for 1 day 0.85 mg/dL, 2 days 0.81 mg/dL, 3 days 0.76 mg/dL (P < 0.05) which means there is a difference in the results of the immediate serum creatinine examination and the stored serum.